The role of endurance exercise and adenosine on monocyte chemotactic protein-1 (MCP-1) gene expression in male rat brain ischemia-reperfusion : Endurance exercise and adenosine on ischemia-reperfusion - Zhou, Liping; Chen, Jiajia; Dong, Xu; Yi, Yang (Cellular and Molecular Biology, 2023)
A suitable exercise program helps to improve physiological performance and improves aerobic capacity, blood absorption, and sufficient oxygen for the brain and muscles. This study investigated the effect of endurance training and adenosine drug injection on the MCP-1 gene after cerebral ischemia and perfusion in male rats. For this purpose, 48 male Wistar rats were selected, and after ischemic induction, they were placed in endurance training/adenosine/ischemia, ischemia/adenosine, endurance training/ischemia, and control/ischemia groups. After induction of ischemia, an endurance exercise protocol was performed. Real-Time PCR technique was used to evaluate monocyte chemotactic protein-1 (MCP-1) gene expression. The results showed a significant difference between the control/ischemia group and the adenosine/ischemia group in the expression of the MCP-1 gene among male rats. Also, there was a significant difference in MCP-1 gene expression between the control/ischemia group and the endurance exercise/ischemia group. On the other hand, there was no significant difference between the control/ischemia group and the endurance training/adenosine/ischemia group in MCP-1 gene expression in ischemia-reperfusion male rats. Overall, it is likely that preconditioning with endurance exercise and adenosine drug up-regulates MCP-1 gene expression before the ischemic stroke. Therefore, training and adenosine may be helpful as preventive stimuli against ischemic stroke.